2016
DOI: 10.1007/s00261-015-0556-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient preferences for chaperone use during transvaginal sonography

Abstract: Approximately half of adult women scheduled to undergo transvaginal pelvic sonography prefer that a chaperone be present if their sonographer is male, but in general do not feel it is necessary if their sonographer is female. These opinions do not change after performance of a transvaginal pelvic ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…The literature is limited and divided on the use of chaperones specifically for male health care providers working with female patients. Only one study conducted in the United States, a 2016 retrospective review of study data including 155 adult female patients, assessed this question and found that approximately half of respondents scheduled for transvaginal pelvic sonography preferred a chaperone if their sonographer was male . However, a 2003 Scottish survey questioned 1000 women about their attitudes toward pelvic examinations and found that 34% actively objected to a chaperone .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature is limited and divided on the use of chaperones specifically for male health care providers working with female patients. Only one study conducted in the United States, a 2016 retrospective review of study data including 155 adult female patients, assessed this question and found that approximately half of respondents scheduled for transvaginal pelvic sonography preferred a chaperone if their sonographer was male . However, a 2003 Scottish survey questioned 1000 women about their attitudes toward pelvic examinations and found that 34% actively objected to a chaperone .…”
Section: Discussionmentioning
confidence: 99%
“…Only one study conducted in the United States, a 2016 retrospective review of study data including 155 adult female patients, assessed this question and found that approximately half of respondents scheduled for transvaginal pelvic sonography preferred a chaperone if their sonographer was male. 15 However, a 2003 Scottish survey questioned 1000 women about their attitudes toward pelvic examinations and found that 34% actively objected to a chaperone. 16 Additionally, the women in this study who reported greater levels of distress regarding the examination were still no more likely to want a chaperone present.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When imaging women, particularly for examinations of the breast and pelvic region, many patients prefer the presence of a female chaperone when a male radiologist or technologist is present (39). In addition, women who live in rural locations may be considered vulnerable and at-risk when it comes to gaining access to essential radiologic screening tools, such as mammography and breast MRI (40).…”
Section: Womenmentioning
confidence: 99%
“…This might be due to embarrassment felt during TVS, even in the presence of a female, which was reported by Davenport et al . [28] The embarrassment experienced is however less than they expected. [29] This is also reflected in the views of 94.8% of postmenopausal women who do not want a third person in the room during TVS.…”
Section: Discussionmentioning
confidence: 99%